P‐207: Research on Improving the ESD Ability of OGS Based on DOE. Issue 1 (2nd June 2017) - Jun, Li; Xi-bin, Shao; Zong-jie, Guo; Qi-cheng, Chen; Lei, Zhang; Liang, Jiang; Rui-feng, Wang; Xun, Cui
Abstract : In this paper, two ESD phenomenon of OGS touch panel were analyzed, that are electrostatic breakdown of black matrix and bridge. Firstly analyzed the principle of electrostatic breakdown of black matrix and metal bridge. Then, Using two‐level factorial designs methods, take the ESD ability of glass surface and sensor surface as response variables, these influence parameters were optimized with factors of cost, transmittance, electrical uniformity etc. and obtained the optimal parameter combination is SiO2 thickness 400 Å, ITO space 100pm, bridge width 10µm, OC2 thickness 2.0µm. Experiment results show that, using the optimized parameters, the ESD ability of glass surface by the original 7 kV up 10 23 kV and sensor surface by the original 2 kV up to 7 kV, as well as, the electrical properties and optical property are all spec in.